Breakfast habits of 1,202 Northern italian children admitted to a summer sport school. Breakfast skipping is associated with overweight and obesity - Vanelli, M.; Iovane, B.; Bernardini, et al., A. (Acta Biomedica Atenei Parmensis, 2005)
Very little is known about the differences in breakfast of children performing physical activity in the morning.This paper analyzed the breakfast habits of 747 boys and 455 girls, distributed in 2 homogeneous age groups, 6-10 and 11-14 year-old, participating in a Summer Sport School. Children were asked whether, when, where, how and with whom they consumed breakfast; who prepared meals; what they ate and drank; what they did during breakfast. Weight, height and BMI were recorded. Seventy-eight percent of children usually had breakfast, but 22% reported skipping breakfast. In the non-breakfast consumer subjects, 27.5% were overweight and 9.6% obese vs 9.1 and 4.5% respectively in breakfast eaters. Bakery products (76%) and milk (71%) were the most frequently consumed foods. Only 15% of parents encouraged their children to consume additional foods at breakfast before exercising, and 42 % of children believed that this extra nutrition was unnecessary. In 80% of cases, the chief decision-maker for breakfast was the mother, the father played little part (1%). During breakfast, 48% of children ate and drank in silence, 26% played with brothers and sisters, 18% watched television and only 8% talked with parents. A high prevalence of overweight and obesity was found among non-breakfast consumer children. Breakfast omission in children exercising conflicts with their increased energy requirements and may be connected to the trend of parents and children to under-estimate the importance of breakfast for nutritional balance and for environment promotion of physical performance.